Analisis Geometri Peledakan untuk Meminimalisir Jarak Lemparan Batuan (Flyrock) pada Peledakan Tambang Terbuka PT Ansar Terang Crushindo II Pangkalan Sumatera Barat Dengan Visualisasi menggunakan Drone DJI Phantom 4 - Suryadi Suryadi; Raimon Kopa (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract. Flyrock is the fragmentation of rocks that are thrown due to result of blasting. Fragmentation of rocks thrown over a safe radius can cause damage to mechanical devices, injuries, and even death to humans. This is what causes the effects of flyrock to be one of the main concerns in every blasting activity. This study aims to analyze the better of geometry in order to reduce the distance of flyrock. The study was conducted on 11 blasting blocks, by comparing the distance of flyrock before and after the geometric changes of the blasting, including seven blasting without simulation and four blasting with the simulation. Observation of the distance of flyrock in detail using DJI Phantom 4 drones and plotting coordinates with GPS (Global Positioning System). Theoretically the distance of rock throws according to the empirical method with the theories of Richard and Moore (2005) is 65 m, and Lundborg (1981) 107.25 m. Whereas according to the method of dimensional analysis with the theory of Ebrahim Ghasemi (2012) it is 110.53 m. Of the seven blasting activities obtained the average distance of rock throws (flyrock) is 143 m with the farthest distance of 160 m. Thus Ebrahim Ghasemi's theory is more representative in predicting the distance of rock throws because it has a smaller difference (22%). Simulation of blasting activities is carried out by changing geometry in stemming depth, because statistically stemming has a very strong relationship to the distance of flyrock (R2 = 0.84), where stemming can control energy in the hole so it is not released upwards in giving rocks to the side. Besides that the increase in stemming causes hole depth to also increase. From the four blasting simulation activities carried out, the average flyrock distance was 53.95 m with the furthest distance 63.2 m. This means that with the simulation the distance of flyrock can be minimized by 89.05 m or about 62.27%.Keywords: Blastability Geometry, Flyrock